# cos(2x)-cos(6x)=sin(8x)

## Simple and best practice solution for cos(2x)-cos(6x)=sin(8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cos(2x)-cos(6x)=sin(8x) equation:

Simplifying
cos(2x) + -1cos(6x) = sin(8x)
Remove parenthesis around (2x)
cos * 2x + -1cos(6x) = sin(8x)
Reorder the terms for easier multiplication:
2cos * x + -1cos(6x) = sin(8x)
Multiply cos * x
2cosx + -1cos(6x) = sin(8x)
Remove parenthesis around (6x)
2cosx + -1cos * 6x = sin(8x)
Reorder the terms for easier multiplication:
2cosx + -1 * 6cos * x = sin(8x)
Multiply -1 * 6
2cosx + -6cos * x = sin(8x)
Multiply cos * x
2cosx + -6cosx = sin(8x)
Combine like terms: 2cosx + -6cosx = -4cosx
-4cosx = sin(8x)
Remove parenthesis around (8x)
-4cosx = ins * 8x
Reorder the terms for easier multiplication:
-4cosx = 8ins * x
Multiply ins * x
-4cosx = 8insx
Solving
-4cosx = 8insx
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Divide each side by '-4osx'.
c = -2ino-1
Simplifying
c = -2ino-1`

## Related pages

roman numerals 100000square root of 0.36250-175least to greatest calculator fractionswhat is the prime factorization of 465x 7 2x 2graph of cos 4xfraction equation solver calculatorgcf of 147roads.advancedacademics.comy 2cosx2.75 as a fractionderivative of e 2tlcm of 2 and 22x 2y 5z 2x y 3z3x 5y 2048.1 is what percent of 240.5prime factorization of 111prime factorization of 180096 prime factorization1944 in roman numeralsx squared minus 9 factoredtwo step equation calculator with fractionswhat is 10 percent of 2000.00square root of 529what is the greatest common factor of 54 and 72roman numerals for 197432 qt gal2xagcf of 56 and 72derivative of 2tx2-2x-63deriv of tantan60graph of y 2x 5x3 2x2100000000 dollarsfactor 2t 2 7t 31975 in roman numerals4n36prime factorization 9897 roman numeralswhat is the prime factorization of 86solve equation with fractions calculatorsolve 3x360 x3gcf of 72 and 9097 roman numeralsroman numerals for 19722cosx 1 0factoring x cubedderivative of 3xgraph y 2x 7prime factorization of 72cos 2 4x sin 2 4x1.8.6100-85117t70-45solve 2x 5y 10prime factorization of 93prime factorization 72144-25what is the lcm of 6 7 92cos2x-1 0ln2-ln11983 in roman numeralsdifferentiate calculator with steps1980 in roman numeralsprime factorization of 1900prime factors of 548x squaredcalculator for multiplying fractions